The Portuguese Language in the Timorese Multilingual Context: Between Staying and Leaving - Soares, Lúcia Vidal (Linha D’Água, 2019)
East-Timor, a young Southeast Asian country that was recognized by its independence at the beginning of the 21st century, after 400 years of Portuguese colonialism and 24 years of Indonesian invasion, is a true linguistic mosaic. This way, we find an “endogenous multilingualism” (CAVALLI et al., 2009), the result of ambulation and miscegenation in that space and an “exogenous multilingualism” (CAVALLI et al., 2009), as a result of the openness of society to diversity, as well as of the interests regarding various economic interests, and, in the sequence, as a consequence of historical-political processes. Currently, The Portuguese Language is one of the co-official languages of that young country after being banned during the Indonesian occupation. In this article, we discuss the relations between the Portuguese and other languages that circulate in that territory, both from the point of view of linguistic policy and from a more personal perspective, within the context of the subjects’ representations. For this purpose, we will use, partly, the study by Soares (2014), based on collected data in the area in 2010, as well as official and unofficial written sources regarding the languages in question.